ANTIFIBROTIC ACTIVITY OF MESNA AGAINST AMIODARONE-ASSOCIATED LUNG INJURY IN WISTAR RATS - Razzaq Mshimesh, Bahir Abdul (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Lung fibrosis is a progressive respiratory disease with a high percentage of mortality. Till now, it had bad prognosis to conventional medications. This study was designed to evaluate the role of mesna, the well-known antioxidant agent, against pulmonary fibrosis. Methods: Pulmonary fibrosis was induced by administration of amiodarone to Wistar rats. Lung indices, leukocytes count, oxidative stress markers, cytokines levels, and hydroxyproline contents, in addition to the histopathological tests, were done for control, amiodarone, and mesna plus amiodarone group. Results: The elevated ratio of lung/body weight and total leukocytes count within bronchoalveolar lavage fluid for amiodarone rats was decline significantly when cotreated with mesna therapy. Furthermore, mesna significantly brought down the lipid peroxidation of amiodarone in lung tissue, represented by decreasing malondialdehyde level and increasing superoxide dismutase (SOD) and catalase activity. In addition, mesna diminished the profibrotic transforming growth factor-Î²1 level while elevated the antifibrotic interferon-Î³ level, and the high activity of the enzyme matrix metalloproteinase-7 was restored within mesna group. Meanwhile, mesna counteracts the increment of hydroxyproline contents and Ashcroft grading scale within amiodarone group. Histologically, critical improvement in the inflammatory cell penetration and alveolar septa was seen in the lung tissue of rats within mesna group, contrasted with those received just amiodarone. Trichome staining clarified that collagen deposition was notably diminished in the peri-alveolar and peri-bronchial area within mesna group. Moreover, mesna therapy downregulated SMAD3 protein level, which was overexpressed by amiodarone challenge. Conclusion: This study gives evidence that mesna therapy may act as a protective agent against amiodarone-mediated pulmonary fibrosis.